2018
DOI: 10.1088/1361-6528/aacede
|View full text |Cite
|
Sign up to set email alerts
|

Surface enhanced Raman scattering substrates prepared by thermal evaporation on liquid surfaces

Abstract: We present an effective surface-enhancement Raman scattering (SERS) substrate enabled by depositing metallic film on a liquid surface at room temperature. Thermal evaporation is used to deposit Au atoms on silicone oil surface and then form quasi-continuous films. Due to the isotropic characteristics of the liquid surface, this film consists of substantial nanoparticles with uniform diameter, which is different from films fabricated on solid substrates and can be served as an applicable substrate for SERS dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Metallic thin films deposited on liquid surfaces have been intensively investigated for decades because of the unique properties and potential applications in optical, electronic, and other interdisciplinary fields. Compared with solid substrates, liquid surfaces possess smaller tangential stress and larger capability of flowing, and thus can be regarded as quasi free-standing substrates . The growth of metallic films on liquid surfaces can be generally described according to the two-stage growth model: in stage I, metallic atoms nucleate over the liquid surfaces to form disk-shaped clusters; in stage II, the clusters diffuse continuously on the liquid surface and finally aggregate .…”
Section: Introductionmentioning
confidence: 77%
“…Metallic thin films deposited on liquid surfaces have been intensively investigated for decades because of the unique properties and potential applications in optical, electronic, and other interdisciplinary fields. Compared with solid substrates, liquid surfaces possess smaller tangential stress and larger capability of flowing, and thus can be regarded as quasi free-standing substrates . The growth of metallic films on liquid surfaces can be generally described according to the two-stage growth model: in stage I, metallic atoms nucleate over the liquid surfaces to form disk-shaped clusters; in stage II, the clusters diffuse continuously on the liquid surface and finally aggregate .…”
Section: Introductionmentioning
confidence: 77%
“…On the other hand, unlike traditional liquid substrates used for the deposition of metal films, Au films deposited on uncured PDMS are more dispersed and can hardly form branched structures to constitute continuous films as on silicone oil or ionized liquid surfaces. According to the typical two-stage growth model of metallic films deposited on liquid substrates [47]: Au atoms are first aggregated and nucleated on liquid substrates, then randomly diffused and merged into branched structures; afterwards, the branched aggregates are gradually connected to form continuous Au films with the increase in nominal thickness. Therefore, it is indicated that the growth process of Au film on uncured PDMS does not completely obey the typical two-stage growth model.…”
Section: Resultsmentioning
confidence: 99%
“… is the normal Raman signal intensity of the R6G; and are the number of R6G molecules on the SERS substrate and a silicon wafer in the laser spot, respectively. Moreover, the number N of R6G for the influence signal was estimated by the following formulas [ 12 , 42 ]: where represents the molar concentration of R6G and represents the volume of R6G solution; is Avogadro constant; indicates the area of R6G distribution; and is the area of laser spot. The preparation method of R6G samples adsorbed on the substrate and measured in the laser spot was identical with controlled measurement conditions.…”
Section: Resultsmentioning
confidence: 99%
“…By varying the deposition parameters during the growth process, the characteristic morphology and growth mechanism of thin films deposited on liquid substrates have been systematically studied. The growth mechanism basically conforms to the two-stage growth model: the metal atoms first nucleated on the liquid surface and then formed quasi-circular aggregates; in the second stage, the aggregates diffused freely on the liquid surface due to random movement and formed ramified structures after collision and rotation [ 5 , 12 ]. This characteristic growth can be mainly attributed to the free-sustained and isotropic liquid substrates, on which the tangential force between the liquid substrates and the metal films is less; thus, the lattice mismatch can hardly happen.…”
Section: Introductionmentioning
confidence: 99%